The winter's tale - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
One of Shakespeare's most popular comedies: Set in Sicily, it revolves around King Leontes who is consumed by his doubts about his wife's loyalty - resulting in jealous murder plots and estranged relationships.
Keywords: Married people -- Drama; Jealousy -- Drama; Sicily (Italy) -- Kings and rulers -- Drama